Evaluation of actuation compatibility and homogeneities for MRI-powered ferromagnetic sphere. (16th December 2016) - Zhang, Peng; Wang, Wendong; Shi, Yikai; Yuan, Xiaoqing
Abstract: MR-compatibility actuations have been widely investigated for the development of robot-assisted devices under the magnetic resonance imaging (MRI). Ferromagnetic components of MRI-powered can be manipulated remotely using the magnetic force or torque induced by MRI or magnetic field environment. However, (1) numerical analysis of the related factors, geometry and magnitude, influencing the ferromagnetic components, and (2) field non-homogeneities when placed in a uniform main magnetic field B 0 are rarely reported. To address the relationship between magnetic force/torque and parameters, different radii of ferromagnetic spheres are required to exert magnetic force and torque with variable magnetic field. Comparison of the field homogeneities error (FHE) under various locations and parameters was investigated. In this study, we present the equivalent model of magnetic field and compare the magnetic force and torque of ferromagnetic sphere under different conditions and provide a safety distance of drive source (ferromagnetic sphere). The numerical models between parameters are established and significant factors were analyzed. Through various parameters of the ferromagnetic sphere, the performance of the numerical model in the magnetic field was evaluated. Cubic polynomial equations were developed to relate magnetic properties of ferromagnetic sphere with R 2 > 0.9506. Field homogeneity was not significantly affected when actuation source was installed in 32 cm away from the isocenter.